Students’ Challenges on Writing Undergraduate Thesis in the College of Business, Administration and Accountancy at Laguna University: Basis for Research Programs - Arceli Benavente; Bianca Mae R. De Asis; Jocelyn B. Malapascua; Julisa P. Adora; Jessica O. Esguerra; Jan Joshua B. Ilagan (International Journal of Education, Teaching, and Social Sciences, 2022)
The majority of academic degrees include thesis projects as part of the overall learning process. Despite efforts by the educational sector to improve students' writing abilities, many students struggle with academic writing. As a result, it is essential to discuss the problems of writing an undergraduate thesis and provide plans to overcome these difficulties. In this study, the researchers determined the students' level of difficulty in writing an undergraduate thesis. The researchers used descriptive correlational research through survey questionnaires to collect, classify, and analyze the data. The data was from 117 undergraduate students, respectively. Frequency, Percentage, Weighted Mean, and Chi-square was used to measure the relationships between variables. The study revealed the relationships between the student's demographic variables and level of difficulty in terms of English Proficiency, Research Methodology, Team Attitude, Research Topic, and Advisor Relationship. While no significant relationship was identified between demographic variables and level of difficulty in terms of time management. Based on the research findings, it was discovered that the highest predictor of what causes students to struggle in writing an undergraduate thesis is the Methodology, while the Advisor Relationship was the least predictor. As a result, a student research program was proposed to act efficiently, providing plans to improve students' research capabilities, resulting in increased productivity and paper quality.